2021
DOI: 10.3389/fnhum.2020.614979
|View full text |Cite
|
Sign up to set email alerts
|

The Error-Related Negativity Predicts Self-Control Failures in Daily Life

Abstract: Adaptive behavior critically depends on performance monitoring (PM), the ability to monitor action outcomes and the need to adapt behavior. PM-related brain activity has been linked to guiding decisions about whether action adaptation is warranted. The present study examined whether PM-related brain activity in a flanker task, as measured by electroencephalography (EEG), was associated with adaptive behavior in daily life. Specifically, we were interested in the employment of self-control, operationalized as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 105 publications
(170 reference statements)
1
23
0
Order By: Relevance
“…Recently, it has been shown that errorbased learning can be more effective than errorless learning approaches in rehabilitation for brain injury patients, improving patient's self-awareness and allowing skill transfer (Ownsworth et al, 2017), thus highlighting the relevance of error detection and correction for clinical conditions. Critically, Overmeyer et al (2021) showed that ERN can predict selfcontrol in real life behavior. Assessing error-related integrity in brain injury patients may be indicative of self-monitoring abilities within specific cognitive domains and thus guide the choice of rehabilitation techniques.…”
mentioning
confidence: 99%
“…Recently, it has been shown that errorbased learning can be more effective than errorless learning approaches in rehabilitation for brain injury patients, improving patient's self-awareness and allowing skill transfer (Ownsworth et al, 2017), thus highlighting the relevance of error detection and correction for clinical conditions. Critically, Overmeyer et al (2021) showed that ERN can predict selfcontrol in real life behavior. Assessing error-related integrity in brain injury patients may be indicative of self-monitoring abilities within specific cognitive domains and thus guide the choice of rehabilitation techniques.…”
mentioning
confidence: 99%
“…In fact, individuals who do not show the typical ERN in the ACC during self-control conflicts also show worse self-control in a food choice task (van der Laan et al, 2014). In addition, a reduced error-related activity in a broader conflict-monitoring network (involving the anterior mid-cingulate cortex, the presupplementary motor area, and anterior insula) during a conflict task in the laboratory even predicts a higher likelihood of failure in daily self-control conflicts, above and beyond what can be predicted by self-reported trait selfcontrol (Krönke et al, 2018;Krönke et al, 2020;Overmeyer et al, 2021). But please note, that as in other research correlating computer-based indicators of cognitive control and more ecologically valid measures of self-control, there association is not unambiguous: Here, a recent study showed that the ERN and other event-related potential failed to predict personal goal progress (Saunders et al, 2022).…”
Section: Identification Of a Self-control Conflictmentioning
confidence: 99%
“…Therefore, sensitivity to affective feedback is assumed to be one determinant of action regulation success (van de Vijver et al, 2011 ; Kaiser et al, 2021 ). Diminished sensitivity toward affective feedback has been associated with maladaptive behavior, such as diminished self-control in daily life (Overmeyer et al, 2021 ). Additionally, blunted neural reactivity toward errors or reward feedback has been observed in several psychological disorders which are characterized by self-regulatory problems, such as substance abuse or pathological gambling (Euser et al, 2013 ; Gorka et al, 2019 ; Li et al, 2020 ).…”
Section: The Role Of Sense Of Agency and Affective Processing For Action Regulationmentioning
confidence: 99%